Pengaruh Kebijakan Harga Obat terhadap Peluang Peredaran Obat Substandar dan Palsu - Agusriana, Rafika; Wikarya, Uka (Jurnal Kebijakan Ekonomi, 2021)
The implementation of National Health Insurance (NHIS; or Jaminan Kesehatan Nasional/JKN)’s policy, increasing patient access to medicine while keeping its budget under tight control, has the potentiality to result in compromising the safety and efficacy of the medicine. Budget constraint and the existing asymmetry information in terms of quality and price of medicines could lead to a moral hazard situation where pharmaceutical companies may produce substandard and falsified medicines to secure their profit. The result of this research using logistic regression analysis showed that despite previous assumptions, medicines included in JKN list are actually having lower probability of falsified or substandard compared to their counterparts, non-JKN medicines. In terms of the relation between price and quality of the medicines, the probability of falsified or substandard medicines increases up to a price level where for the poor qualified medicines does not have the ability to copy the original medicines while still making profit out of it. As a result, this research recommends full implementation of JKN to include all essential medicines into its list to avoid asymmetry information and maintain medicines quality. JKN also needs to have a price-differentiation policy which allows pharmaceutical companies to maintain quality of their medicines, even to innovate for a better one, while still maintaining a good profit and their ability to compete in the JKN era.